Bianco come mimesi, allusione, fusione. Bernini, Borromini… Mies van der Rohe - Sturm, Saverio (Opus Incertum, 2017)
There is a series of various meanings and intentions which led the foremost masters of Baroque architecture to choose the colour white as the characterising element for certain environments. Bernini choses the monochrome palette for interior spaces destined to the nobility, but more often searches, through the grain and chromatic purity of Roman travertine, the ideal of a “naturalised” architecture, as mimesis of the natural world. Grafted instead with erudite allegorical references, Borromini’s candid architecture does not want to represent an imitative or narrative nature, but rather a convincing allusion to the acting forces, to the dramatic tensions and symbolic meanings that pervade it. A possible synthesis between the two positions is identifiable in the work of Ludwig Mies van der Rohe, notwithstanding the evident contextual difference. His obsessive attention to detail and technical solutions recalls Borromini’s methods, whereas his use of colours is closer to Bernini. Only in the case of Farnsworth House did Mies choose a purely white architecture: a deliberate neutralisation of the building elements, with the purpose of ceding the main role to the surrounding nature, thus allowing a visual and ideal fusion with the polychromatic nature of the Illinois forest.